Those bones are not my child - Bambara, Toni Cade 1939-1995 (Vintage Books, 2000)
In Atlanta, a black woman searches for her missing son with help from volunteers of the city's committee to stop child murders. Suspected is a Ku Klux Klan porn ring. A look at the lot of the black working class in urban America.